IMPROVING PERFORMANCE THROUGH REST TIME SYSTEM DESIGN: PHYSIOLOGICAL INTEGRATION AND QUALITY FUNCTION DEVELOPMENT - Johan Alfian Pradana (Universitas Airlangga, 2021)
Overwork is the cause of above-normal pulses. Rest time role needed to re-normalize pulse. The research aims to design the right rest system with a Physiology and Quality Function Deployment approach in tofu craftsmen of the male gender in Kediri district. The method with the first stage performs measurements of pulse, oxygen consumption, metabolism, energy and intervention. The second stage performs a set of attributes needs of craftsmen and technical responses from MSME owners know with the final results of attribute selection based on the highest weight. The results showed an effective rest time of 233.9 minutes per 6 hours of work reviewed from the physiological approach. Rest time with Quality Function Deployment approach weighing 192.02 is worship with a time of 20 minutes; sleep weight 182.25 with a time of 60 minutes; evaluation weighed 157.84 with a time of 120 minutes; heating weighs 152.96 with a time of 20 minutes; and drinking water weighed 121.85 with a time of 13.9 minutes. With this result, a break design system can be applied to improve the performance of tofu craftsmen. Subsequent development may lead to reduced rest time but result in greater performance.